Becoming Mexipino : multiethnic identities and communities in San Diego - Guevarra, Rudy P., Jr (Latinidad., 2012)
Becoming Mexipino is a social-historical interpretation of two ethnic groups, one Mexican, the other Filipino, whose paths led both groups to San Diego, California from 1900 to 1965. Rudy Guevarra traces their earliest interactions under Spanish colonialism, when they did not strongly identify as Mexican or Filipino, to illustrate how these historical ties and cultural bonds laid the foundation for what would become close interethnic relationships and communities in twentieth-century San Diego as well as in other locales throughout California and the Pacific West Coast. Using archival sources.